Surgical Management of Myofibroma of the Gengiva. Issue 7 (October 2016) - Demo, Paolo Garzino; Savoini, Matteo; Marchetti, Marco; Maletta, Francesca; Zavattero, Emanuele; Ramieri, Guglielmo
Abstract : Abstract: The purpose of this paper is to report a rare patient of oral myofibroma in a 12-year old patient and to describe its clinical, histopathologic, and immunohistochemical features to establish the correct diagnosis and surgical management. Pathological and immunohistochemical examination is a mandatory method for establishing a definitive diagnosis of this lesion avoiding unnecessary treatment. Surgical excision and careful postoperative observation should be a treatment option.